2010
DOI: 10.1536/ihj.51.221
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Albumin Levels and In-Hospital Adverse Outcomes in Acute Coronary Syndrome

Abstract: SummaryEpidemiological studies have demonstrated an association between low serum albumin levels and coronary heart disease and mortality. Nevertheless, the impact of a low serum albumin level during acute coronary syndrome has not yet been established. The aim of the present study was to investigate whether low serum albumin levels are associated with adverse outcomes in acute coronary syndrome. We enrolled 82 consecutive patients with acute coronary syndrome from whom venous blood for serum albumin measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Serum albumin is one of the classical markers determining nutritional status, and a low serum albumin level upon admission can predict in-hospital adverse outcomes in ACS [26]. Multivariate regression analysis in our study showed that albumin was independently associated with Gensini score, which is in agreement with previous studies [27–29].…”
Section: Discussionsupporting
confidence: 92%
“…Serum albumin is one of the classical markers determining nutritional status, and a low serum albumin level upon admission can predict in-hospital adverse outcomes in ACS [26]. Multivariate regression analysis in our study showed that albumin was independently associated with Gensini score, which is in agreement with previous studies [27–29].…”
Section: Discussionsupporting
confidence: 92%
“…ACS patients represent a heterogeneous clinical group. Hypoalbuminemia was associated with angiographic no-reflow after primary percutaneous coronary intervention in patients with STEMI [20] and in-hospital adverse outcomes in non-ST elevation ACS [21]. Moreover, analysis of serum albumin level by continuous variables in patients with first-onset acute myocardial infarction, each 1 g/dl albumin level reduction exhibited a 66 and 47% higher risk of all-cause mortality and cardiovascular death, respectively [13].…”
Section: Discussionmentioning
confidence: 97%
“…Hypoalbuminemia (< 3.5 g/dL) measured upon admission was associated with in-hospital adverse events, including death, acute heart failure, cardiogenic shock, and reinfarction. This association, however, is not significant by adjusting other risk factors (OR: 2.8, 95% CI: 0.7–9.5) [ 42 ] Oduncu et al retrospectively analyzed 1706 patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI), and reported that hypoalbuminemia is associated with both in-hospital mortality and long-term mortality, with a median follow-up of 40 months (23.3 vs. 8.4%, P < 0.001). In a multivariate model, hypoalbuminemia independently predicted long-term mortality (HR: 2.98, 95% CI: 1.35–6.58) [ 39 ].…”
Section: Serum Albumin and Prognosis In Cardiovascular Diseasementioning
confidence: 99%